PENGARUH LATIHAN TABATA WORKOUT TERHADAP PENINGKATAN KEBUGARAN JASMANI SISWA SMP NEGERI 13 KOTA LUBUKLINGGAU USIA 13-15 TAHUN - Wawan Syafutra; M.Trio Suprayogo; Sri Anggraini ($$8@@&&$%K, 2022)
The purpose of this study was to determine whether there was an effect of tabata workout on increasing the physical fitness of students of SMP Negeri 13 Lubuklinggau City aged 13-15 years after being given the Tabata Workout exercise treatment. This research is an experimental research that uses the One Group Pretest Posttest Design. The population in this study were all student members of SMP Negeri 13 Lubuklinggau City. The sample selected using the Random Sampling technique, amounting to 10 people. The data analysis used is the t-test statistic. The instrument used in this research is by using a stopwatch and a whistle. The results of the initial test mean that scores 10-13 are in the Less (K) classification for 4 people, Scores 14-17 for the Moderate category (S) for 4 people, Scores 18-21 are in the Good category (B) for 2 person and the final test with Mean Scores 10-13 are in the Less (K) classification of 0 people, Scores 14-17 are in the Moderate (S) category of 2 person, Scores 18-21 are categorized as Good (B) by 3 people, Scores 22-25 are in the category Very Good (BS) as many as 5 people. From these results there is a difference of 3 children with a t count value of 7.679 and a t table value of 2.0150 with a significance of 0.00 <0.05. So it can be concluded that the training method has the effect of tabata workout on increasing physical fitness at SMP Negeri 13 Lubuklinggau